Nuclear terrorism and virtual risk: Implications for prediction and the utility of models. (2nd May 2017) - Downes, Robert J.; Hobbs, Christopher
Abstract: Assessing the risk of nuclear terrorism is a challenging task due to the diversity of actors involved, variety of pathways to success, range of defensive measures employed, and the lack of detailed historical record upon which to base analysis. Numerical models developed to date vary wildly in both approach and ultimate assessment: estimates of the likelihood a nuclear terrorist attack differ by up to nine orders of magnitude. This article critiques existing efforts from the standpoint of probability theory, and proposes an alternative perspective on the utility of risk assessment in this area. Nuclear terrorism is argued to be a 'virtual risk' for which it is not possible to meaningfully ascribe a quantitative measure, making numerical estimates of the likelihood of nuclear terrorism misleading. Instead, we argue that focus should be placed on utilising models to identify areas of disagreement as targets for further research, with greater emphasis on understanding terrorist decision-making and adaption in response to nuclear security measures.